Role of Femvertising in Enhancing Women’s Empowerment in FMCG Brand Campaigns - Rose Martin, Preethy; Shanthi, R. (International Research Journal of Business Studies, 2024)
Advertisements that endorse and empower women and girls are referred to as “Femvertising”. These advertisements frequently defy stereotypes and portray women in powerful and competent roles. The study explored the contribution of Femvertising in women’s empowerment. This empirical study aimed to look at three key indicators of women’s empowerment: Autonomy, Self-efficacy, and Gender role equality exhibited in advertisement campaigns. The three brands chosen for analysing these three indicators were Hamam, Horlicks and Vim. Data was gathered through a structured questionnaire from 188 respondents. The study found that self-efficacy significantly influences perceived women’s empowerment. Gender role equality attitude varied with the Educational attainment. Additionally, self-efficacy partially mediated the relationship between gender role equality and perceived women’s empowerment, while autonomy moderated the link between self-efficacy and gender role equality, with high autonomy weakening the association. These results underscore Femvertising's potential to reshape societal perceptions and promote women's empowerment through empowering commercials.